2015
DOI: 10.1038/srep15503
|View full text |Cite
|
Sign up to set email alerts
|

Vagal modulation of high mobility group box-1 protein mediates electroacupuncture-induced cardioprotection in ischemia-reperfusion injury

Abstract: Excessive release of high mobility group box-1 (HMGB1) protein from ischemic cardiomyocytes activates inflammatory cascades and enhances myocardial injury after reperfusion. Here we report evidence that electroacupuncture of mice at Neiguan acupoints can inhibit the up-regulation of cardiac HMGB1 following myocardial ischemia and attenuate the associated inflammatory responses and myocardial injury during reperfusion. These benefits of electroacupuncture were partially reversed by administering recombinant HMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…At 24 hr after MI/R injury, myocardial infarct size was measured by Evans blue‐TTC double staining . In brief, the suture beneath the left coronary artery was re‐tied, and perfusion of Evans blue dye was achieved by injecting 0.2 mL 2% Evans blue into the left ventricular cavity, with the dye uniformly distributed except in the ischemic area (area at risk, AAR).…”
Section: Methodsmentioning
confidence: 99%
“…At 24 hr after MI/R injury, myocardial infarct size was measured by Evans blue‐TTC double staining . In brief, the suture beneath the left coronary artery was re‐tied, and perfusion of Evans blue dye was achieved by injecting 0.2 mL 2% Evans blue into the left ventricular cavity, with the dye uniformly distributed except in the ischemic area (area at risk, AAR).…”
Section: Methodsmentioning
confidence: 99%
“…HMGB1, originally described as a DNA-binding protein and passively released by necrotic cells and actively released by macrophages/monocytes, was discovered to be an essential cytokine that mediates the response to infection, injury, and inflammation [51] . Our previous animal study has shown that EA can inhibit excessive release of HMGB1 following myocardial ischemia and attenuate the associated inflammatory responses and myocardial injury during reperfusion [52] . Recently, HMGB1 was found to directly enhance immune inhibitory functions of Treg and limit the number and activity of conventional T cells [53,54] .…”
Section: The Quantification Of Mhla-dr Expression Shows the Best Predmentioning
confidence: 98%
“…Disruption of parasympathetic activity is a common hallmark of a variety of cardiovascular diseases including AMI [ 5 ]. The results from preclinical studies have shown that increased vagal activity exerts cardioprotective effects against myocardial I/R injury [ 6 , 7 , 8 , 9 , 10 ]. At cellular level, ACh, a neurotransmitter of the cardiac vagus nerve, is the chemical released which acts as a stimulus for the modulation of the parasympathetic activity involved in both electrical and mechanical functions of the heart [ 11 , 12 , 41 ].…”
Section: Parasympathetic Modulation As a Novel Strategy For Attenumentioning
confidence: 99%
“…The beneficial effects of GTS21 were blocked when co-administered with MLA, suggesting that GTS21 treatment decreased the infarct size and improved cardiac contractile function through the activation of α7nAChR [ 55 ]. In addition, Zhang et al have also demonstrated that the infarct size in mice hearts pretreated with electroacupuncture at the Neiguan acupoint (PC6) was significantly reduced compared with the control [ 8 ]. Additionally, the serum cardiac troponin I was significantly decreased after electroacupuncture.…”
Section: The Effects Of α7 Nicotinic Acetylcholine Receptor (α7nacmentioning
confidence: 99%
See 1 more Smart Citation